Diagnosis and management of Marchiafava–Bignami disease: a review of CT/MRI confirmed cases. Issue 2 (26th August 2013) - Hillbom, Matti; Saloheimo, Pertti; Fujioka, Shinsuke; Wszolek, Zbigniew K; Juvela, Seppo; Leone, Maurizio A
Abstract : Objective: Marchiafava–Bignami disease (MBD) is a rare condition mainly associated with alcoholism, although it may be mimicked by several other disorders that cause corpus callosum lesions. Our objective was to identify helpful features for differential diagnosis and assess whether any treatment can be recommended. Methods: We reviewed 122 reports containing data on 153 subjects with confirmed MBD that was associated with either alcoholism or malnutrition, and 20 reports with data on 53 subjects with conditions mimicking MBD. All the cases had been verified antemortem by brain imaging. Unconditional logistic regression was used to demonstrate factors that were associated with the outcome of MBD. Results: The mimicking conditions were differentiated from MBD by the occurrence of solitary and rapidly disappearing splenial lesions; fewer signs and symptoms with exception of seizures, hemiparesis and tetraparesis; nystagmus; and rapid and complete recovery. MBD occurred most frequently among alcoholics, but it was also reported in 11 non-alcoholics (7.2% of all the MBD cases). A better outcome was observed among those who were treated within 2 weeks after onset of symptoms with parenteral thiamine (p=0.033). Conclusions: As thiamine deficiency is frequently associated with alcoholism, malnutrition and prolonged vomiting; we recommend prompt treatment of MBD with parenteral thiamine in such subjects. Recovery should be followed by repeated neuropsychological and MRI examinations, preferably using diffusion tensor imaging.